2015
DOI: 10.1186/s12866-015-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the integrons of metallo-β-lactamase-producing Pseudomonas aeruginosa isolates collected by nationwide surveillance programs across Japan

Abstract: BackgroundWe investigate the evolving molecular epidemiology of metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa isolates collected in a 100 institution, nationwide surveillance study in Japan from 2004 to 2006.ResultsMBL-producers were detected in 23/996 isolates (2.3%) in 2004 and 21/992 (2.1%) in 2006. Antimicrobial resistance (specifically, carbapenem resistance) rates between two periods did not differ significantly. MBL-producers were more prevalent in urinary tract isolates. blaIMP-1 group was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
(42 reference statements)
3
32
2
3
Order By: Relevance
“…We found these MBL‐producing P. aeruginosa isolates were highly resistant to most antibiotics examined, except CL. In the relationship between P. aeruginosa and MBL genes, IMP‐1 isolated in Japan were highly resistant to all β‐lactams, aminoglycoside and fluoroquinolones; however, the present data showed that AMK had some possibility as a therapeutic strategy for this (susceptibility rate: 18/21, 85.7%). In addition, CL was also added as a therapeutic strategy for carbapenem‐resistant Gram‐negative bacteria infections .…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…We found these MBL‐producing P. aeruginosa isolates were highly resistant to most antibiotics examined, except CL. In the relationship between P. aeruginosa and MBL genes, IMP‐1 isolated in Japan were highly resistant to all β‐lactams, aminoglycoside and fluoroquinolones; however, the present data showed that AMK had some possibility as a therapeutic strategy for this (susceptibility rate: 18/21, 85.7%). In addition, CL was also added as a therapeutic strategy for carbapenem‐resistant Gram‐negative bacteria infections .…”
Section: Discussioncontrasting
confidence: 61%
“…Our MBL‐producing P. aeruginosa isolates were typed into IMP‐1, IMP‐7 or VIM‐1, and those with IMP‐1 were first discovered worldwide in the late 1980s and spread to Japan in 1991 . To date, the isolates with IMP‐1 have mainly spread in Asian regions . P. aeruginosa with VIM‐1 or IMP‐7 was also first found in 1999 or 2002, respectively, and has been found in Asian regions (isolated in Japan in 2010) and European regions as well .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations